The role of the special education itinerant teacher : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Banks, Rebecca Jane (Massey University, 2013)
This research is a qualitative case study examining the roles and responsibilities of the Special Education Itinerant Teacher on the support team of a student with very high and complex needs enrolled at a small, semi-rural, culturally diverse primary school. It utilises the ideas of social constructionism, that our 'reality' is constructed through our relationships and interactions with others. According to this paradigm knowledge about the role of the SEIT, like all knowledge, is co-constructed by the interactions and dialogue of the student's support team. Therefore semi-structured interviews with open-ended questions were conducted with 9 participants who made up key members of the student's support team. Some relevant documentation was also gathered. The data collected was analysed inductively for emerging patterns in the narratives around the activities of the support teacher and each participant's experience of the support. The data indicated that the support of the SEIT was greatly valued by all participants, but a construction of two separate systems of education -regular for the regular kids, and 'special' approaches for students with high and complex needs, presented barriers to inclusion and genuine collaboration between all members of the team. These barriers are discussed, along with a number of supports which were also identified.
Page iv (Contents page) missing from print and electronic copies.
Keywords: Special education; Special education teacher